2019
DOI: 10.1186/s13071-019-3466-z
|View full text |Cite
|
Sign up to set email alerts
|

Immune response profile of caruncular and trophoblast cell lines infected by high- (Nc-Spain7) and low-virulence (Nc-Spain1H) isolates of Neospora caninum

Abstract: Background Bovine neosporosis, one of the main causes of reproductive failure in cattle worldwide, poses a challenge for the immune system of pregnant cows. Changes in the Th-1/Th-2 balance in the placenta during gestation have been associated with abortion. Cotyledon and caruncle cell layers form the maternal-foetal interface in the placenta and are able to recognize and induce immune responses against Neospora caninum among other pathogens. The objective of the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 63 publications
3
19
0
Order By: Relevance
“…This result is quite remarkable, since pro-inflammatory cytokines have been implicated in host defence during N. caninum infection [1-3, 15, 16], and they lead to enhanced control of Nc-Spain1H growth and dissemination. In addition, in previous in vitro studies, we showed stronger stimulation of the immune response in bovine macrophages [12] and trophoblast cells [9,11] infected by Nc-Spain1H than in those infected by Nc-Spain7. How placental tissues can recognize and mount an appropriate immune response against this isolate is a fascinating question whose answer remains unknown.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This result is quite remarkable, since pro-inflammatory cytokines have been implicated in host defence during N. caninum infection [1-3, 15, 16], and they lead to enhanced control of Nc-Spain1H growth and dissemination. In addition, in previous in vitro studies, we showed stronger stimulation of the immune response in bovine macrophages [12] and trophoblast cells [9,11] infected by Nc-Spain1H than in those infected by Nc-Spain7. How placental tissues can recognize and mount an appropriate immune response against this isolate is a fascinating question whose answer remains unknown.…”
Section: Discussionsupporting
confidence: 60%
“…Previously, we used in vitro and in vivo models to characterize two N. caninum isolates with marked differences in virulence: Nc-Spain7 and Nc-Spain1H, previously classified as high-and lowvirulence isolates, respectively [6][7][8]. Specifically, in bovine trophobast cells [9][10][11] and macrophages [12], Nc-Spain7 showed an increased infection and proliferation rates, whereas Nc-Spain1H displayed a reduced proliferation associated to a higher stimulation of immune responses. However, in vitro models cannot mimic the complex architecture of the bovine placenta, as they lack the microenvironmental influences and the host ability to compensate for stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed certain immune responses of trophoblast cells to infection. However, perhaps due to a lack of stimulation of other immune cells or even due to the limitations of the analysis technique, we were not able to find key elements such as cytokines widely studied by other authors in placental cells [6,[36][37][38]. No clear differences were found between isolates, corroborating the results previously found by gene expression analyses in the same model of N. caninum [6].…”
Section: Host Immune Response During N Caninum Infectionsupporting
confidence: 85%
“…Trophoblast cells are a recognized component of the immune system and are capable of responding to pathogens [32,33]. Recently, it has been shown by quantitative PCR analyses that trophoblast cells are able to respond to Neospora infection with a pro-inflammatory cytokine expression profile [6]. In the present study, none of these immune-related proteins were identified.…”
Section: Host Immune Response During N Caninum Infectionmentioning
confidence: 49%
See 1 more Smart Citation